Upinder Singh, A History of Ancient and Early Medieval India. From Stone Age to the 12th Century, Delhi, Pearson, 2009, 677 pp. - Yver Alonso Melchor Hernández (El Colegio de México, A.C., 2014)
Upinder Singh, A History of Ancient and Early Medieval India. From Stone Age to the 12th Century, Delhi, Pearson, 2009, 677 pp.